2020
DOI: 10.20525/ijrbs.v9i2.623
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ workplace well-being and work engagement of divine word colleges’ employees in Ilocos region, Philippines

Abstract: The purpose of the study was to determine the correlation between workplace well-being and work engagement of Divine Word Colleges’ employees in the Ilocos Region. In order to support the study, theories were presented and related literature and studies were reviewed. The study used a descriptive correlational research design. The respondents of the study were all employees of the Colleges. In carrying out the study, validated questionnaires were used and in tabulating and interpreting the data, weighted mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
3
13
0
2
Order By: Relevance
“…This study also confirmed the recent study by Abun et al (2020), contended that genuine respect and empathy from the organization in the form of inclusive management that cares for the individual employee can boost the morale and engagement of employees in an organization (Abun, et. al 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study also confirmed the recent study by Abun et al (2020), contended that genuine respect and empathy from the organization in the form of inclusive management that cares for the individual employee can boost the morale and engagement of employees in an organization (Abun, et. al 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Firstly in terms of context supportive elements such as support from supervisor, co-worker, a well-designed and conducive work environment. Secondly, in terms of holistic subjective well-being development elements such as skill and knowledge, character and personal values, the purpose of life, faith, and spiritual growth, as well as positive and meaningful friendship in the workplace (Abun et al, 2020). Our study found that inclusive management in term of context supportive elements are fully mediated by the holistic subjective well-being development elements in influencing the employee engagement.…”
Section: Discussionmentioning
confidence: 56%
“…As a result, it should become an organizational culture consistently implemented by management toward their employees and employees toward management. Respect is seen as a fundamental human right in philosophy and ethics (Abun, Magallanes, Foronda, & Encarnacion, 2020). Potter (2014), a hierarchy will most likely be the dominating management approach without respect for collaboration.…”
Section: Organizational Respectmentioning
confidence: 99%
“…Third, workplace well-being is an employee's need that the company must meet. Therefore, workplace well-being is a variable of great concern considering that the fulfillment of workplace well-being will improve the quality of the work of the workers themselves (Abun et al, 2020;Aryanti et al, 2020;Maulana, 2018;Zahro, 2018). Page (2005) explained that workplace well-being is based on the intrinsic and extrinsic values of work.…”
Section: Introductionmentioning
confidence: 99%